Research on Human-Machine Interaction Technology for Intelligent Mine Collaborative Operation Management System - LI Xionghui; HAO Bo; LI Cheng; JIANG Xuezhai; TIAN Deqiang; CHEN Xiaoxuan (Kongzhi Yu Xinxi Jishu)
In order to ensure the safe and efficient operation of driverless mining trucks in open-pit mines, this paper focuses on the human-machine interaction (HMI) technology applied in the collaborative operation management system for these autonomous systems to implement loading, unloading, and auxiliary tasks collaboratively. The introduced HMI technology supports voice control, lateral distance control, and secondary shovel engagement in the loading operation scenario, concentrated on improving loading accuracy and efficiency while safeguarding operational safety. The functions of dumping area control and road/retaining wall auxiliary operations are introduced in the unloading operation scenario, to realize accurate control in the unloading process and mitigate potential safety risks. Auxiliary operation functions such as real-time dynamic voice prompts, obstacle clearing, path display, radar views, distance warning, and positioning anomaly warning, further enhance the functionality and practicality of the cooperative operation management system. This technology has been practically applied in an open-pit mine, and the results showed that the additional functions of the cooperative management system bolstered by the HMI technology enhanced the safety of the driverless systems and elevated operational efficiency.